Methodology fundamentals for investigating violations of the laws and customs of war - O. O. Khan; O. V. Manyk (Bulletin of Kharkiv National University of Internal Affairs)
Based on modern ideas on the concept of forensic methods of specific crimes investigation, their classification according to the level of generalisation of information contained therein and their structure, the article considers theoretical prerequisites for developing methods of investigation of violations of the laws and customs of war. The relevance of scientific developments in this area has been substantiated. Based on the definition of the criminal law classification of criminal acts included in the concept of "violation of the laws and customs of war", the author concludes that it is advisable to develop subspecies methods of investigation of crimes of certain types included in this concept.